Effects of some angiospermic plant extracts on in vitro vegetative growth of Fusarium moniliforme - Yasmin, M; Hossain, KS; Bashar, MA (Bangladesh Journal of Botany, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Fifty five angiospermic plants were selected for evaluating the effect of their aqueous extracts on the in vitro vegetative growth of Fusarium moniliforme Sheldon. Extracts of 17 plants showed varied degrees of inhibitory effects on the test pathogen. For instance the leaf extract of Lawsonia inermis showed maximum inhibition (60.65 %) followed by roots of Asparagus racemosus (50.59 %). The possibility of using these plant extracts in seed treatment to control bakanae disease of rice is suggested. Antifungal property of leaves of Andrographis paniculata and Lagerstroemia speciosa against bakanae disease is reported here for the first time. Key words: In vitro, Vegetative growth, Bakanae, Fusarium moniliforme, Plant extracts doi:10.3329/bjb.v37i1.1569 Bangladesh J. Bot. 37(1): 85-88, 2008 (June)